2017
DOI: 10.31472/ihe.5.2017.01
|View full text |Cite
|
Sign up to set email alerts
|

Perspectiveness and Development of Apparatus the Principle of Work Is Based on the Mechanisms of Discrete-Pulse Energy Input

Abstract: The article presents new developments, in particular, is equipment for neutralization of acid condensates of gas combustion products in heating and industrial boiler houses and a new cavitation type extractor. The article described principle of work and the results of experimental studies are presented which confirm the effectiveness to application of equipment in various industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Considering in detail the process of the acidic condensate formation and the reason for the equilibrium of the system "water -carbonic acid" at a concentration of carbonic acid much higher than equilibrium, it was hypothesized that carbon dioxide in the condensate is contained in a dissolved state and in the form of stable bubbles of micro-and nanoscales, being in equilibrium with carbonic acid (16). The obtained results indicate that the course of the process of degassing of acidic condensate is close to the process of degassing of the model solution.…”
Section: Resultsmentioning
confidence: 99%
“…Considering in detail the process of the acidic condensate formation and the reason for the equilibrium of the system "water -carbonic acid" at a concentration of carbonic acid much higher than equilibrium, it was hypothesized that carbon dioxide in the condensate is contained in a dissolved state and in the form of stable bubbles of micro-and nanoscales, being in equilibrium with carbonic acid (16). The obtained results indicate that the course of the process of degassing of acidic condensate is close to the process of degassing of the model solution.…”
Section: Resultsmentioning
confidence: 99%
“…Меõàí³çìè ДІÂЕ бóлè òеîðеòè÷íî äîñл³äжеí³ â ðîбîòàõ [10][11][12], à òеõíîлîг³÷í³ òà ³íжеíеðí³ äîпîâíеííя цüîгî ìеòîäà íàâеäеí³ â ðîбîòàõ [13][14][15][16] òà óçàгàлüíеí³ â ðîбîòàõ [17][18].…”
Section: маòер³али òа ìеòодиunclassified
“…Це ñпðè÷èíяє п³äâèщеííя ñòàб³лüíîñò³ гîòîâîї УÂÂÏ, пðèçâîäèòü äî çì³íè äèíàì³êè гîð³ííя òà äîäàòêîâîгî çíèжеííя âèêèä³â NOx òà CO2. Тàêèé ñпîñ³б îäеðжàííя УÂÂÏ пîêðàщóє ðеîлîг³÷í³ òà ñеäè-ìеíòàц³éí³ âлàñòèâîñò³ пàлèâà, çíèжóє шê³äлè-â³ âèêèäè пðè гîð³íí³, âплèâàє íà пàðàìеòðè гî-ð³ííя [10].…”
Section: тèп îблàäíàííяunclassified
“…1, it can be concluded that the most effective oxygen absorption in the AORT installation is in 1 cycle at a pulsation frequency of 2.8 kHz. Under such processing conditions, the content of dissolved oxygen in water reaches 7.9 mg/dm 3 . Further studies on the influence of DPEI mechanisms and design features of the apparatus on oxygen absorption were carried out on residential and communal wastewater.…”
Section: Employees Of the Institute Of Technicalmentioning
confidence: 99%